Changes in stroking parameters associated with an increase in front crawl speed at high level - Huot-Marchand, F.; Sidney, M.; Hellard, P.; Alberty, M.; Caudal, N.; Knopp, M.; Pelayo, P. (First international symposium sciences and practices in swimming, 2006)
The purpose of this study was to analyze the changes in temporal parameters associated with an increase in swimming speed at high-level. The population was composed by 98 male and 109 female swimmers, twice finalists at the French championships in one year of interval, within the 1998-2004 period. The results show that increasing preferentially the stroke length is not the main observed stroking adaptation in a long-term Progression. Indeed, all strategies have been observed and each can induce an increase in the swimming speed at high level. However, it can also be noticed that the bilateral strategy consisting in increasing moderately both the stroke rate and the stroke length seems to be associated with the highest increases in swimming speed.